Image Dehazing Techniques: A Survey - HARPREET kAUR (International Journal of Advanced Science and Technology, 2020)
Dehazing is a mechanism of eliminating the degration from the picture to enhance itsclearity.Sincepresence of haze in the atmosphere introduces some kind of noise in an image or itsimply diminishes the visibility of a scene,it becomes vital to remove this problem. Remote sensingdeals with the usage of satellite or airplaneimages, which are based on sensor technology for thedetection of various resources on earth such as its surface, ambiance and data about oceans.However, this technique of sensing the resources or objects faces certain tribulations regarding thequality of the image. In thispaper,detailed information is given of the haze noise along with thevarious techniques to eliminatethis noise from an image that can be used in the future or are alreadyin use.